Intelligent information retrieval. (9th May 2006) - Curran, Kevin; Murphy, Cliona; Annesley, Stephen
Web intelligence combines the interaction of the human mind and artificial intelligence with networks and technology. This paper attempts to define and summarise the concept of web intelligence, highlight the key elements of web intelligence, and explore the topic of web information retrieval with particular focus on multimedia/information retrieval and intelligent agents.